FEMINISMS AND VISUAL ARTS: WHAT IS DISCUSSED IN XXI CENTURY BRAZILIAN POST-GRADUATION/FEMINISMOS E ARTES VISUAIS: O QUE SE DISCUTE NA PUS-GRADUAQAO BRASILEIRA DO SECULO XXI? - Sardelich, Maria Emilia; Nascimento, Fernanda S (Revista Ártemis (João Pessoa), 2020)
This article aims to map and analyze discussion on the feminisms of Brazilian postgraduate academic production in Visual Arts. Through a systematic bibliographical revision, it explores the Brazilian Digital Thesis and Dissertations Library (Biblioteca Digital Brasileira de Teses e Dissertacoes-BDTD), of the Brazilian Institute of Science and Technology (Instituto Brasileiro de Ciencia e Tecnologia-IBICT), in the time period between 2000 and 2019. The content analysis of twenty-nine master theses and six doctoral dissertations has categorized some tendencies in this production, such as: feminist poetics, feminist readings, revisionist strategies and feminist approaches. These are works animated by an epistemology of difference, to which the world, the knowledge produced about it, is not reduced to the logic of a universal subject, but of subjectivities more or less constrained by disciplinary and control practices, by institutional discourse and knowledges, inserted in complex social relations, which break the conceptual normative framing of gender and sexuality. Keywords: Feminisms. Visual Art. Feminist Critique. Feminist Poetics. Feminist Readings. Este artigo tem por objetivo mapear e analisar as discussoes sobre os feminismos na producao academica da Pos-graduacao brasileira em Artes Visuais. Por meio de uma revisao bibliografica sistematica, foi explorada a Biblioteca Digital Brasileira de Teses e Dissertacoes (BDTD), do Instituto Brasileiro de Ciencia e Tecnologia (IBICT), no recorte temporal de 2000 a 2019. A analise do conteudo de vinte e nove dissertacoes de mestrado e seis teses de doutorado categorizou algumas tendencias nessa producao, como: poeticas feministas, leituras feministas, estrategias revisionistas e aproximacoes feministas. Sao trabalhos animados por uma epistemologia da diferenca, para a qual o mundo e o conhecimento produzido sobre ele nao sao reduzidos a logica da identidade de um sujeito universal, mas de subjetividades constrangidas, nao raro, por praticas disciplinadoras e de controle, por discursos e saberes instituintes, que se inserem em complexas relacoes sociais, rompendo um enquadramento normativo-conceitual de genero e sexualidade. Palavras-chave: Feminismos. Artes-visuais. Critica feminista. Poetica feminista. Leitura feminista.